Unraveling cardiolipin-induced conformational change of cytochrome c through H/D exchange mass spectrometry and quartz crystal microbalance - Sin-Cih Sun (Nature Portfolio, 2021)
Abstract Cardiolipin (CL), a crucial component in inner mitochondrial membranes, interacts with cytochrome c (cyt c) to form a peroxidase complex for the catalysis of CL oxidation. Such interaction is pivotal to the mitochondrial regulation of apoptosis and is affected by the redox state of cyt c. In the present study, the redox-dependent interaction of cyt c with CL was investigated through amide hydrogen/deuterium exchange coupled with mass spectrometry (HDXMS) and quartz crystal microbalance with dissipation monitoring (QCM-D). Ferrous cyt c exhibited a more compact conformation compared with its ferric form, which was supported by the lower number of deuterons accumulated and the greater amplitude reduction on dissipation. Upon association with CL, ferrous cyt c resulted in a moderate increase in deuteration, whereas the ferric form caused a drastic increase of deuteration, which indicated that CL-bound ferric cyt c formed an extended conformation. These results were consistent with those of the frequency (f) − dissipation (D) experiments, which revealed that ferric cyt c yielded greater values of |ΔD/Δf| within the first minute. Further fragmentation analysis based on HDXMS indicated that the effect of CL binding was considerably different on ferric and ferrous cyt c in the C-helix and the Loop 9–24. In ferric cyt c, CL binding affected Met80 and destabilized His18 interaction with heme, which was not observed with ferrous cyt c. An interaction model was proposed to explain the aforementioned results.